Physical security with power beacon assisted in half-duplex relaying networks over Rayleigh fading channel: performance analysis - Phu Tran Tin; Duy-Hung Ha; Luu Gia Thien; Tran Thanh Trang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
In this research, we proposed and investigated physical security with power beacon assisted in half-duplex relaying networks over a Rayleigh fading channel. In this model, the source (S) node communicates with the destination (D) node via the helping of the intermediate relay (R) node. The D and R nodes harvest energy from the power beacon (PB) node in the presence of a passive eavesdropper (E) node. Then we derived the integral form of the system outage probability (OP) and closed form of the intercept probability (IP). The correctness of the analytical of the OP and IP is verified by the Monte Carlo simulation. The influence of the main system parameters on the OP and IP also is investigated. The research results indicated that the analytical results are the same as the simulation ones.